A facile method for synthesis of novel phenyl phosphates flame retardants and their application in epoxy resin. Issue 44 (13th September 2022) - Guo, Yong; Rong, Hu; Yu, Yuan; Chen, Tingting; Chen, Zhongwei; Suo, Yifan; Zhang, Qingwu; Li, Changxin; Jiang, Juncheng
Abstract: Piperazinyl phenyl phosphate (PPOP) and 4, 4‐diaminodiphenylmethyl phenyl phosphate (DPOA) containing phosphorus and nitrogen elements as flame retardants applied for epoxy resin (EP) were successfully synthesized, and substantiated by Fourier transform infrared spectra (FTIR), 1 H and 31 P nuclear magnetic resonance (NMR) and elemental analysis (EA). The limiting oxygen index (LOI) of the EP composites with 3 wt% of PPOP and DPOA attained 33.6% and 34.2%, both acquired the UL‐94 V‐0 rating, respectively. The peak of heat release rate (pHRR), the total heat release (THR) and the total smoke production (TSP) of EP/PPOP‐1 decreased by 21.0%, 25.6%, and 18.7%, respectively. For EP/DPOA‐1, the pHRR, THR, and TSP were brought down by 23.5%, 21.8%, and 26.4%, respectively. Flame‐retardant mechanisms were explicitly evaluated by the scanning electron microscope (SEM), Raman spectroscopy and thermogravimetric analysis‐infrared spectrometry (TG‐IR). This proposed method not only could produce efficient flame retardant for EP but provide new ideas for replacing existing halogenated flame retardants. Abstract :